PEMBENTUKAN INDEKS MIDDLE INCOME TRAP DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA TAHUN 2015-2018 - Zaradia Permatasari; Ernawati Pasaribu (Politeknik Statistika STIS, 2020)
Indonesia experiences demographic dividend throughout 2017-2030. However, the momentum of demographic dividend experienced by Indonesia is accompanied by the development of the 4.0 industrial revolution. The demand for labor is decreasing due to the existence of artificial intelligence and advanced robotics which replace human labor. So, the risk of unemployment becomes higher. This has aggravated the situation in which Indonesia is trapped in a middle-income trap. Whereas other countries can take advantage of demographic dividend so as to encourage the economy. This study reveals the existence of middle income trap at the provincial level based on their economic capacity by forming a middle income trap index. In addition, this study statistically tests whether this high unemployment rate due to demographic devidend causes Indonesia not be able to escape the middle income trap. During 2015 to 2018, there are 20 provinces that fall into MIT and 14 provinces that did not. The test results show that the adult unemployment rate and gini ratio have positive and significant effects on the MIT index, while the formation of gross fixed capital, the gross enrollment rate of universities, and the growth of gross value added in the manufacturing sector have negative and significant effects on the MIT index.